The Sandwich Structure of the Southern Yellow Sea Cold Water Mass and Yellow Sea Warm Current - Fei, Yu; Qiang, Ren; Xinyuan, Diao; Chuanjie, Wei; Yibo, Hu (Frontiers in Marine Science, 2022)
The southern Yellow Sea cold water mass (YSCWM) and Yellow Sea warm current (YSWC) are prominent features in the southern Yellow Sea. The traditional viewpoint is that the southern YSCWM exists in the warm half of the year and the YSWC exists in the cold half of the year; most existing studies have regarded these features as independent ocean phenomenon. Through marine investigations conducted in recent years in the southern Yellow Sea, the southern YSCWM was found to exist in early winter in 2010, and the YSWC was observed in early summer in 2013,2014. For approximately half the year, the southern YSCWM and YSWC existed simultaneously, and the YSWC was located in a slightly high-temperature region in the middle of the southern YSCWM. A sandwich-shaped temperature structure formed in the middle of the southern Yellow Sea from spring to autumn. This paper studies the seasonal variation characteristics of the 3-dimensional southern YSCWM and YSWC structures using ocean survey data collected in recent years. The new perspective of the seasonal variations in the southern YSCWM and YSWC obtained herein will promote the recognition of southern Yellow Sea water exchanges and support biogeochemical cycle research in the Yellow Sea.